Intellectual Phishing, Hidden Conflicts of Interest and Hidden Data: New Risks of Preprints - Jaime A. Teixeira da Silva (Centre for Behaviour and Wellness Advocacy, 2017)
Preprints were originally destined to put forward a first version of a version of a paper that was prepared, as best and complete as possible, by the authors, but for which they wanted intellectual input from the community prior to submission to a regular peer reviewed journal. Although arXiv has led the way with physics and mathematics, bioRxiv became popular for the biological sciences. Since the beginning of 2016, after a preprint promotional campaign by ASAPbio, the popularity of preprints has been increasing, as has the number of preprint servers. Three fairly recent (March and May of 2017) preprints published in bioRxiv test the limits and uses of preprints, and bring with them a whole set of ethical questions. The three reprints were published primarily by members of the publishing elite, leaders of ethical bodies and think tanks aiming to establish new rules or guidelines, to address several issues in research integrity and ethics. However, in at least two cases, the texts are in a fairly crude state of intellectual development, and the authors are explicitly using bioRxiv to "fish" for ideas from peers and the public. It is unclear how any individual / group who contributes intellectually to such preprints will be acknowledged, if at all, and the risks of ghost authorship exist with this new exploratory model of preprints. In addition, the use of preprints to accommodate the intellectual ideas of others, while taking all the credit, may be a new form of academic scam in publishing, "intellectual phishing." Risks to the integrity of publishing are already high, and if preprints are seen as being abused in any way, then this may reduce trust in this new academic model. The risk is compounded by the discovery of multiple hidden conflicts of interest in these and one other preprint.